At Westonci.ca, we connect you with the best answers from a community of experienced and knowledgeable individuals. Join our platform to get reliable answers to your questions from a knowledgeable community of experts. Join our platform to connect with experts ready to provide precise answers to your questions in different areas.
Sagot :
To find the value of \( b \) in the given system of linear equations, let's solve the system step-by-step.
The given system of equations is:
[tex]\[ \begin{aligned} a - b + c &= -6 \quad \text{(1)} \\ b - c &= 5 \quad \text{(2)} \\ 2a - 2c &= 4 \quad \text{(3)} \end{aligned} \][/tex]
We start by simplifying equation (3):
[tex]\[ 2a - 2c = 4 \implies a - c = 2 \quad \text{(4)} \][/tex]
Now we have:
[tex]\[ \begin{aligned} a - b + c &= -6 \quad \text{(1)} \\ b - c &= 5 \quad \text{(2)} \\ a - c &= 2 \quad \text{(4)} \end{aligned} \][/tex]
From equation (2):
[tex]\[ b - c = 5 \implies b = c + 5 \quad \text{(5)} \][/tex]
We will substitute \( b = c + 5 \) from equation (5) into equations (1) and (4).
First, substitute \( b = c + 5 \) into equation (1):
[tex]\[ a - (c + 5) + c = -6 \implies a - c - 5 + c = -6 \implies a - 5 = -6 \implies a = -1 \quad \text{(6)} \][/tex]
Next, substitute \( a = -1 \) into equation (4):
[tex]\[ -1 - c = 2 \implies c = -1 - 2 \implies c = -3 \quad \text{(7)} \][/tex]
Now, we substitute \( c = -3 \) back into equation (5) to find \( b \):
[tex]\[ b = c + 5 \implies b = -3 + 5 \implies b = 2 \][/tex]
Thus, the value of \( b \) is \( 2 \).
The correct answer is:
[tex]\[ \boxed{2} \][/tex]
The given system of equations is:
[tex]\[ \begin{aligned} a - b + c &= -6 \quad \text{(1)} \\ b - c &= 5 \quad \text{(2)} \\ 2a - 2c &= 4 \quad \text{(3)} \end{aligned} \][/tex]
We start by simplifying equation (3):
[tex]\[ 2a - 2c = 4 \implies a - c = 2 \quad \text{(4)} \][/tex]
Now we have:
[tex]\[ \begin{aligned} a - b + c &= -6 \quad \text{(1)} \\ b - c &= 5 \quad \text{(2)} \\ a - c &= 2 \quad \text{(4)} \end{aligned} \][/tex]
From equation (2):
[tex]\[ b - c = 5 \implies b = c + 5 \quad \text{(5)} \][/tex]
We will substitute \( b = c + 5 \) from equation (5) into equations (1) and (4).
First, substitute \( b = c + 5 \) into equation (1):
[tex]\[ a - (c + 5) + c = -6 \implies a - c - 5 + c = -6 \implies a - 5 = -6 \implies a = -1 \quad \text{(6)} \][/tex]
Next, substitute \( a = -1 \) into equation (4):
[tex]\[ -1 - c = 2 \implies c = -1 - 2 \implies c = -3 \quad \text{(7)} \][/tex]
Now, we substitute \( c = -3 \) back into equation (5) to find \( b \):
[tex]\[ b = c + 5 \implies b = -3 + 5 \implies b = 2 \][/tex]
Thus, the value of \( b \) is \( 2 \).
The correct answer is:
[tex]\[ \boxed{2} \][/tex]
We hope this information was helpful. Feel free to return anytime for more answers to your questions and concerns. Thank you for your visit. We're committed to providing you with the best information available. Return anytime for more. Westonci.ca is your go-to source for reliable answers. Return soon for more expert insights.